Mobilising intensive care patients early - Xi Wern Ling; Yee Hua Lim; Hwee Kuan Ong; Vimal Palanichamy; Kenneth Bao Ren Leong; Xi Yun Ling; Ken Cheah Hooi Lee; Vui Kian Ho (Proceedings of Singapore Healthcare, 2021)
Background: Early mobilisation in the intensive care unit has been suggested to improve outcomes. However, safety and practical concerns have led to the slow uptake of early mobilisation. Objectives: We designed a study to evaluate the practicability and efficacy of an early mobilisation protocol in intensive care unit patients. Methods: We performed a prospective non-blinded observational cohort study based on a quality improvement project. We implemented a protocol for early mobilisation of suitable patients admitted to medical and surgical intensive care units of a tertiary care hospital. All other aspects of patient care were managed as usual. Patients were followed up to discharge. Data were collected from July to August 2016 pre-implementation and from November 2016 to February 2017 following protocol implementation. The primary outcome measure was the mobilisation rate, defined as the number of days mobilised divided by the number of days each patient met mobilisation criteria. Secondary outcome measures included adverse event rate, length of mechanical ventilation, intensive care unit and hospital stay, intensive care unit and inhospital mortality and discharge destination. Results: A total of 312 patients were analysed, of which 60% were men with a mean age of 63.4 years. Following early mobilisation implementation, the mobilisation rate increased from 39% to 65% ( P =0.006). The percentage of patients discharged home increased from 49.0% to 75.9% ( P <0.001). Mortality, length of mechanical ventilation, length of stay and adverse event rate did not differ significantly. Conclusion: The implementation of an early mobilisation protocol in our intensive care unit was both safe and effective without requiring additional staffing. Efforts are ongoing to increase compliance with the protocol.